Review of non-Helicobacter pylori Helicobacter species: Insights into pathogenesis, epidemiology, and clinical implications - M. Kroiß; B. Teodorescu; T. Song; R. Vasapolli (Microbiota in Health and Disease)
Non-Helicobacter pylori Helicobacters (NHPHs) represent a group of bacteria distinct from H. pylori. They are commonly found in the gastrointestinal tracts of animals, such as poultry, swine, and domestic pets. Recent studies have demonstrated that these organisms have implications beyond animal hosts, indicating a potential role in human gastric diseases and raising concerns about the possibility of zoonotic transmission. Different NHPH species can cause gastritis, ulcerations, and even systemic effects like bacteremia in human individuals. A comprehensive literature search protocol on MEDLINE (PubMed) from the last twelve months was employed, resulting in the identification of 24 articles and case studies on NHPHs in animals and 12 in humans, respectively. Furthermore, we conducted a search for Helicobacter species other than H. pylori that are referenced individually in the National Library of Medicine database. The most recent studies have focused on the clinical manifestations and diagnostic challenges of NHPHs-related diseases in animal models and human cases. An important subject was the transmission of disease between different species, particularly those associated with livestock farming. The results suggest that NHPHs, especially H. pullorum, H. suis, and H. cinaedi, may be a significant contributing factor in the development of gastrointestinal diseases in humans, particularly in instances where H. pylori is not present. Although there has been a significant improvement in the overall awareness regarding NHPH infections, it remains a challenge to identify new species and distinguish between low and high pathogenicity levels. Further research is needed to understand how NHPH impacts human health, with a focus on improved diagnostic tools and treatment strategies.